Impact of M&A has on the share price - Vasconcelos, Francisco Ferreira (2020)
Throughout the years, in the airline sector there has been several M&A deals. The firm acquiring and the one being acquired may see changes in its share price. The hypothesis being tested is that the firm being acquired sees its share price boost and the acquiring one maintains the same share price as before the deal. In order to prove this hypothesis two M&A deals were analyzed, and the acquired firm sees its share price boost.